EX-LIBRIS IN THE WORK OF LEV GETS - Ґах , Ірина (Art and Design, 2024)
Purpose of the Ukrainian-Polish artist Lev Gets, which are presented as the subject of art historical research for the first time, are the object of scientific exploration. Methodology is based on the use of compositional, stylistic, structural-logical and historical analyses. In the investigation, a comprehensive approach to the review of visual sources using chronological and source-scientific methods is applied. Results allow us not only to supplement the history of the development and popularization of the book sign of the 1930s, but also to introduce Lev Getz's bookplates into the Ukrainian art historical debate, to present his contribution to the creation and dissemination of the book sign in the first half of the twentieth century. The article investigates the themes and features of the artist's bookplate creation, identifies the main formal and substantive component in the context of exhibition projects of Ukrainian painting in the first half of the twentieth century, in particular, the activities of the Circle of Ukrainian Art Workers (НDUM). The attention is focused on those book marks of L. Getz that represent the author's style, represent the figurative and semantic character of the works and indicate the high professional level of the artist. The features of his artistic style of interpretation of form, composition, and coloristic solution of small forms graphics are highlighted. For the first time, the bookplates of Lev Getz are presented as one of the most interesting stages of the artist's formation, which significantly influenced his further creative activity. Scientific novelty consists in the introduction of the little-known graphic works of Lev Gets into Ukrainian art history, and, operating with archival documents and photographic materials from the funds of the Historical Museum of Sianyok (Poland), the archives of the Institute of National Remembrance (Poland) and the library of oo. Basilian in Rome (Italy) for the first time to present the bookplates of the artist as a subject of research. Practical presented material will serve as the beginning of the next stage of thorough research of Lev Gets work and the publication of little-known graphic works of the artist.